Approaches to Measuring the Activity of Major Lipolytic and Lipogenic Enzymes In Vitro and Ex Vivo - Wilhelm, Marek; Rossmeislová, Lenka; Šiklová, Michaela (International journal of molecular sciences, 2022)
Since the 1950s, one of the goals of adipose tissue research has been to determine lipolytic and lipogenic activity as the primary metabolic pathways affecting adipocyte health and size and thus representing potential therapeutic targets for the treatment of obesity and associated diseases. Nowadays, there is a relatively large number of methods to measure the activity of these pathways and involved enzymes, but their applicability to different biological samples is variable. Here, we review the characteristics of mean lipogenic and lipolytic enzymes, their inhibitors, and available methodologies for assessing their activity, and comment on the advantages and disadvantages of these methodologies and their applicability in vivo, ex vivo, and in vitro, i.e., in cells, organs and their respective extracts, with the emphasis on adipocytes and adipose tissue.
Keywords: obezita; activity measurement; tuková tkáň; fatty-acid synthase; hormone-sensitive lipase; Adipocytes; Obesity; inhibitor; lipogeneze; tukové buňky; Humans; Lipolysis; Lipogenesis; lidé; acetyl-CoA carboxylase; Adipose Tissue; adipose triglyceride lipase; lipolýza